Risk Factors and Scabious Prevalence in Cats During 2020 in Griya Satwa Clinic, Magetan - Cahya, Nedriana; Primarizky, Hardany; Yunita, Maya Nurwartanti (Universitas Airlangga, 2022)
Scabious is a disease that often infests cats, originating from the family Sarcoptidae. This study aimed to determine the prevalence and factors that can affect the risk of scabious in cats. The study was evaluated at the Griya Satwa Clinic, Magetan in January-February 2021. The design of this study was a retrospective cohort study by taking secondary data during the 2020 period as study material. The data obtained were then entered into the Statistical Package for the Social Sciences (SPSS) version 20 for windows to analyze the association's relationship and increased risk by calculating the Chi-Square and Odds Ratio. The samples obtained were 76 cats infested with scabious. The analysis of the association of risk factors for scabious was breed (P = 0.428), age (P = 0.793), sex (P = 0.426). The results of the prevalence of scabious in cats from the study during January-February 2021 in the 2020 period were 9.5%, and the analysis of the association (Chi-Square) and the increased (Odds Ratio) of factors including breed, age, sex on the risk of scabious in cats were not significance / absent influence, The probability of error obtained is outside the tolerance set by the researcher, so the results are not significant (p>0,05).